L'homosexualité masculine et féminine et 50 témoignages inédits - Hahn, Pierre; Meignant, Michel; Pittenger, Norman (Paris: Filipacchi, 1978)
"Pierrre Hahn; Michel Meignant; Norman Pittenger... et al. Fonds Suzan Daniel (FSD)"